Intraspecific Variations in Ecomorphological Functional Traits of Montane Stream-Dwelling Frogs Were Driven by Their Microhabitat Conditions - Xiwen Peng; Da Kang; Guangfeng Chen; Suwen Hu; Zijian Sun; Tian Zhao (Animals)
Understanding how habitat conditions drive morphological adaptations in animals is critical in ecology, yet amphibian studies remain limited. This study investigated intraspecific variation in ecomorphological traits of three montane stream-dwelling frogs (Quasipaa boulengeri, Amolops sinensis, and Odorrana margaratae) across elevation gradients in Tianping Mountain, China. Using morphological measurements and environmental variables collected from ten transects, we analyzed functional traits related to feeding and locomotion and assessed their associations with microhabitat variables. Significant trait differences between low- and high-elevation groups were detected only in Q. boulengeri, with high-elevation individuals exhibiting greater body mass and shorter hindlimbs. Redundancy analysis demonstrated that microhabitat variables, particularly air humidity, flow rate, and rock coverage, were linked to trait variations. For example, air humidity and flow rate significantly influenced Q. boulengeri’s body and limb proportions, while flow rate affected A. sinensis’s snout and limb morphology. In addition, sex and seasonal effects were also associated with trait variations. These results underscore amphibians’ phenotypic plasticity in response to the environment and highlight the role of microhabitat complexity in shaping traits. By linking habitat heterogeneity to eco-morphology, this study advocates for conservation strategies that preserve varied stream environments to support amphibian resilience amid environmental changes.